Decentralized Choice of Monitoring Systems. - Demski, Joel S.; Patell, James M.; Wolfson, Mark A. (The Accounting Review, 1984)
This paper presents an agency model in which one of several monitoring systems can be chosen, if the agent possesses private information about the firm's production technology, the principal may rationally prefer to delegate the choice of the monitor to the agent even though the agent's compensation will depend on the monitoring information. In general, this expansion of the contracting space allows the principal to orchestrate more efficiently the agent's effort and monitoring system choices. The model suggests that the existence of alternative accounting methods and the delegation of their selection to management may represent rational equilibrium behavior.